Economic System Convergence in Globalization Era and Its Implication on Renewal and Economic Law in Indonesia - Purwanto Purwanto; Charlyna S Purba (International Journal of Multi Discipline Science, 2018)
Conflicts of interest between developed and developing countries can not be avoided in economic globalization. In the fight, there is domination and hegemony of economic concentration by economic actors from developed countries. The convergence of an accommodative economic system, which does not separate categorically between the capitalistic and socialist market economies, needs to be considered in the reform of Indonesian economic law.